Stephen Massey: a career in visual neuroscience - Mills, Stephen L.; Marshak, David W. (Frontiers in Ophthalmology, 2023)
This review is a memoir by Dr. Stephen C. Massey’s longtime collaborator, Dr. Stephen L. Mills, and written, for the most part, in the first person. It also serves as an introduction to the virtual festschrift to celebrate Dr. Massey’s retirement. and. The references cited here are only a few of the highlights of Dr. Massey’s distinguished career. A complete list is found here: https://pubmed.ncbi.nlm.nih.gov/?term=massey+sc+%28retina+or+photoreceptors%29&sort=date.